2007
DOI: 10.1111/j.1600-0854.2007.00650.x
|View full text |Cite
|
Sign up to set email alerts
|

A Heparan Sulfate‐Facilitated and Raft‐Dependent Macropinocytosis of Eosinophil Cationic Protein

Abstract: †These authors contributed equally to this work.Eosinophil cationic protein (ECP), a human RNAseA superfamily member, highly implicated in asthma pathology, is toxic to bronchial epithelial cells following its endocytosis. The mechanism by which ECP is internalized into cells is poorly understood. In this study, we show that cell surface-bound heparan sulfate proteoglycans serve as the major receptor for ECP internalization. Removal of cell surface heparan sulfate by heparinases or reducing glycan sulfation by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 72 publications
6
68
0
Order By: Relevance
“…Cell ELISA-The ability of MBP-ECP to bind cells in the presence of serial dilutions of oligosaccharides or peptides was determined as described (9). Briefly, confluent monolayers of Beas-2B cells in 96-well plates were pretreated with various concentrations of oligosaccharides or peptides in serum-free RPMI 1640 medium at 4°C for 30 min before incubation with 5 g/ml MBP-ECP at 4°C for 1 h. The cells were then washed with ice-cold PBS and fixed with 2% paraformaldehyde at room temperature for 15 min prior to blocking with 2% bovine serum albumin/PBS at room temperature for 90 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell ELISA-The ability of MBP-ECP to bind cells in the presence of serial dilutions of oligosaccharides or peptides was determined as described (9). Briefly, confluent monolayers of Beas-2B cells in 96-well plates were pretreated with various concentrations of oligosaccharides or peptides in serum-free RPMI 1640 medium at 4°C for 30 min before incubation with 5 g/ml MBP-ECP at 4°C for 1 h. The cells were then washed with ice-cold PBS and fixed with 2% paraformaldehyde at room temperature for 15 min prior to blocking with 2% bovine serum albumin/PBS at room temperature for 90 min.…”
Section: Methodsmentioning
confidence: 99%
“…The binding of ECP to target cells has been attributed to its high arginine content (estimated pI ϭ 10.8), which facilitates the interaction between ECP and negatively charged molecules on the cell surface (7,8). Recently, we found that binding and endocytosis of ECP into bronchial epithelial cells were greatly dependent on the cell surface glycosaminoglycan, specifically heparan sulfate proteoglycans (HSPG) (9). The cytotoxicity of ECP was severely reduced toward cell lines with heparan sulfate (HS) deficiency.…”
mentioning
confidence: 99%
“…The timing of EGFR co-localization with EEA1-containing endosomes was delayed, which could be due to the altered ubiquitylation and subsequent endocytosis of the receptors associated with HSPG in TERM. Syndecans are known to mediate endocytosis of heparin-binding ligands and proteins (e.g., FGF2 or eosinophil cationic protein) by macropinocytosis (42,43). This pathway is slow and involves formation of uncoated vesicles that eventually fuse with sorting endosomes.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the 33 -38 stretch is involved in ECP binding to GAGs ( Figure 2) (Fan et al , 2008 ;Torrent et al , 2011a ). The protein interaction with heparan sulphate at the matrix of epithelial cells would facilitate the protein endocytosis (Fan et al , 2007 ). Further insight on the protein residues potentially involved in heparin binding has been deduced by molecular docking as detailed below.…”
Section: Dissecting Ecp Antimicrobial Mechanism Of Actionmentioning
confidence: 99%